E-MONEY BANYUWANGI TOURISM : QR CODE SEBAGAI ALAT TRANSAKSI DI WISATA PULAU MERAH - Yashinta Setyowati; Ayu Nadia Ramadhani; Muhamad Bayu A; Debby Ratna Daniel; A.A Gde Satia Utama (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
This study aims to design a sales system using QR Code as a means of transactions in the tour of Red Island. One of the tourist attractions in Banyuwangi often visited by foreign and domestic tourists is the Red Island. The advantages of the Red Island is the waves that are always stable for surfing, clean and conducive environment, and amazing scenery. However, due to the large number of visitors, it is not comparable with the sellers and service providers, the low educational background makes local residents difficult to communicate especially with foreign tourists. This research uses qualitative exploratory and action research methods conducted in Pulau Merah. Data collection is done through interviews and in-depth observation. Data analysis is done to generate a system requirement that will be designed. The result of this research is the design of sales accounting information system using QR Code as transaction tool. The contribution of this research is to increase the income of the people around Red Island, as well as local government through tax revenue, also to improve the competitiveness of Red Island into a natural tourist area of technology. Keyword : E-Money, QR Code, Accounting Information System of Sales, EBusiness